Toward the identification of cyano-astroCOMs via vibrational features: benzonitrile as a test case - Xu, Yanting; Biczysko, Malgorzata (Frontiers in Chemistry, 2024)
James Webb Space Telescope (JWST) opened a new era for the identification of molecular systems in the interstellar medium (ISM) by vibrational features. One group of molecules of increasing interest are cyano derivatives of aromatic organic molecules, which have already been identified in the ISM on the basis of the analysis of rotational signatures, and so are plausible candidates for the detection by the JWST. The benzonitrile considered in this work represent a suitable example for the validation of a computational strategy, which can be further applied for different, larger and not-yet observed molecules. For this purpose anharmonic simulations of infrared (IR) spectra have been compared with recent FTIR experimental study ( J. Quant. Spectrosc. Radiat. Transfer (2022) 283, 108159). The anharmonic computations employing GVPT2 in conjunction with hybrid force field combining harmonic part from revDSD-PBEP86-D3/jun-cc-pVTZ with anharmonic corrections from B3LYP-D3/SNSD show very good agreement with experiment, with mean error of 11 cm -1 for all fundamental transitions on overall, and only 2 cm -1 for the C≡N stretching fundamental at 4.49 µm. Inclusion of overtones up to three-quanta transitions allowed also prediction of spectra in the near-Infrared region, which shows distinct features due to C≡N overtones at the 2.26 µm and 1.52 µm. Remarkable accuracy of GVPT2 results opens a pathway for reliable prediction of spectra for broader range of cyano-astroCOMs.